Plasminogen Activator Inhibitor-1 and Adiponectin Are Associated With Metabolic Syndrome Components. (15th September 2021) - Vecchiola, Andrea; García, Killén; González-Gómez, Luis M; Tapia-Castillo, Alejandra; Artigas, Rocío; Baudrand, René; Kalergis, Alexis M; Carvajal, Cristian A; Fardella, Carlos E
Abstract: BACKGROUND: We aimed to study the associations of adipocytokines, endothelial damage markers, and high-sensitivity C-reactive protein (hs-CRP) with metabolic syndrome (MetS) components. METHODS: This cross-sectional study included 202 subjects categorized into MetS and No-MetS according to Harmonizing Adult Treatment Panel III. RESULTS: Subjects with MetS showed higher levels of proinflammatory molecules but significantly lower adiponectin levels than subjects with No-MetS. Among the studied adipocytokines, plasminogen activator inhibitor-1 (PAI-1) and adiponectin showed the strongest associations with most MetS components. PAI-1 was associated with MetS (odds ratio (OR) 1.107 (1.065–1.151), P < 0.0001), whereas adiponectin was inversely associated with MetS (OR 0.710 (0.610–0.825), P < 0.0001). Following adjustment by sex, age, body mass index, and 24-hour urinary sodium excretion in a multivariate analysis, the association of PAI-1 (OR 1.090 (1.044–1.137), P < 0.0001) and adiponectin (OR 0.634 (0.519–0.775), P < 0.0001) with MetS remained significant. Multivariate analyses supported a model in which systolic blood pressure (BP) could be predicted by PAI-1, hs-CRP, and matrix metalloproteinase 2 ( R 2 = 0.125; P = 0.04); diastolic BP ( R 2 = 0.218; P = 0.0001) and glucose ( R 2 = 0.074; P = 0.0001) could be predicted by PAI-1; waist circumference could be predicted by PAI-1 and hs-CRP ( R 2 = 0.28; P = 0.016). Receiver operating characteristic curve analysis showed that a PAI-1 concentration had the best sensitivity and specificity for discriminating subjects with MetS. CONCLUSION: PAI-1 and adiponectin rendered the most robust associations with MetS components in a general population, indicating that unfavorable adipose tissue performance is a key contributor to these metabolic anomalies. Further prospective analyses should allow establishing whether these adipocytokines can anticipate the progress of MetS and cardiovascular risk.